Grammaticality Judgement in English among Typically Developing Primary School Children: A Preliminary Investigation - Varghese, Reya Ann; Venkatesh, Lakshmi (Journal of All India Institute of Speech and Hearing, 2020)
The present study assessed grammaticality judgment abilities among typically developing children in English in the Indian context. Grammaticality judgment was studied using sentence acceptability and sentence correction tasks in two groups of children; one group of children studying in grade II (7-yearolds’) and another group of children studying in grade V (10-year-olds’). Results revealed a developmental trend in performance of the two groups of children on the two grammaticality judgment tasks in English. Consistent with earlier findings from English speaking children, word order reversals were easier to detect in sentence acceptability task and also easier to correct relative to other errors in sentences such as morpheme deletions and wrong syntactic agreements for children in both grades.The current study provided preliminary developmental data on syntactic awareness task of grammaticality judgments in typically developing children within the Indian context. Such developmental data has may be used for developing protocols for assessing metalinguistic performance of children with language impairments and language based learning disabilities in comparison to typically developing children.